A cohort study of local excision followed by adjuvant therapy incorporating a contact X‐ray brachytherapy boost instead of radical resection in 180 patients with rectal cancer. (8th March 2019) - Smith, F. M.; Pritchard, D. M.; Wong, H.; Whitmarsh, K.; Hershman, M. J.; Sun Myint, A.
Abstract: Aim: Recent data have suggested near‐equivalent oncological results when treating early rectal cancer by local excision followed by radio‐ ± chemotherapy rather than salvage radical surgery. The aim of this retrospective study was to assess the use of contact X‐ray brachytherapy within this paradigm. Method: All patients had undergone local excision and were referred to our radiotherapy centre for treatment with contact X‐ray brachytherapy. Postoperative (chemo)radiotherapy was also given in their local hospital in most cases. Variables assessed were local excision method, postoperative therapy received, follow‐up duration, disease‐free survival, salvage surgery and stoma‐free survival. Results: In total, 180 patients with a median age of 70 (range 36–99) years were assessed. Following local excision, pT stages were pT1 = 131 (72%), pT2 = 44 (26%), pT3 = 5 (2%). All patients received contact X‐ray brachytherapy boosting at our centre and, in addition, 110 received chemoradiotherapy and 60 received radiotherapy alone. After a median follow‐up of 36 months (range 6–48), 169 patients (94%) remained free of local recurrence. Of the 11 patients with local recurrence (three isolated nodal), five underwent salvage abdominoperineal excision. Eight patients developed distant disease, of whom five underwent metastasis surgery. At last included follow‐up 173 (96%) patients were free of all disease and 170 (94%) were stoma free. Conclusions: Contact therapy can be offered in addition to external beam radio (±chemo) therapy instead of radical surgery as follow‐on treatment after local excision of early rectal cancer. This combination can provide equivalent outcomes to radical surgery. The added value of contact therapy should be formally assessed in a clinical trial.